2021
DOI: 10.1093/mnras/stab930
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy-lens determination of H0: the effect of the ellipse + shear modelling assumption

Abstract: Galaxy lenses are frequently modeled as an elliptical mass distribution with external shear and isothermal spheres to account for secondary and line-of-sight galaxies. There is statistical evidence that some fraction of observed quads are inconsistent with these assumptions, and require a dipole-like contribution to the mass with respect to the light. Simplifying assumptions about the shape of mass distributions can lead to the incorrect recovery of parameters such as H0. We create several tests of synthetic q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…It remains to be proved that its conclusions hold for more general models. For example, it is crucial to evaluate the influence of the main lens's satellites, and the offset between baryonic matter and dark matter within the lens [43]. Neglecting such details might lead one to bias, over-constrain, or mis-interpret the shear, similarly to how one may over-constrain H 0 by relying on simplistic lens models in time-delay cosmography [44,45].…”
Section: Cosmic Shear With Strong Lensesmentioning
confidence: 99%
“…It remains to be proved that its conclusions hold for more general models. For example, it is crucial to evaluate the influence of the main lens's satellites, and the offset between baryonic matter and dark matter within the lens [43]. Neglecting such details might lead one to bias, over-constrain, or mis-interpret the shear, similarly to how one may over-constrain H 0 by relying on simplistic lens models in time-delay cosmography [44,45].…”
Section: Cosmic Shear With Strong Lensesmentioning
confidence: 99%
“…Alternatively, the SPLE + ES lens scenario might be an oversimplification of the actual one, since all SPLE + ES models indicate that there is a mass/light misalignment. While this misalignment may be true, it could also be due to the presence of nonmodeled components such as substructures and/or companions of G (e.g., Sluse et al 2012;Gomer & Williams 2021). Further refinement of the lens scenario along with an extension and improvement of the set of observational constraints (future deep photometry and spectroscopy is a pending task of special relevance) will contribute to an accurate determination of H 0 and other cosmological parameters (e.g., Bonvin et al 2017;Birrer et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The only issue with all SPLE + ES mass models is the existence of a significant mass/light misalignment, i.e., the light and mass distributions of the lens galaxy do not match. This misalignment could be genuine or due to an oversimplification of the lens scenario (e.g., Sluse et al 2012;Shu et al 2016;Gomer & Williams 2021). Most early-type galaxies reside in overdense regions, so external tidal fields in their vicinity are expected to have relatively high amplitudes.…”
Section: Lens Mass Models and Hubble Constantmentioning
confidence: 99%
“…In a companion paper of this work, Cao et al (2021) fitted this model to strong lenses simulated using mass models derived from dynamical models of nearby SDSS-IV MaNGA (Bundy et al 2015) early type galaxies and showed this can bias the measurement of the local density slopes around the Einstein ring by 13%. Gomer & Williams (2021) and Van de Vyvere et al (2021) discuss how departures from ellipticity symmetry may affect H 0 inference in lensed quasars. Nightingale et al (2019) have also showed that departures from ellipticital symmetry are observed in the luminous emission of three strong lenses.…”
Section: O R I Gmentioning
confidence: 99%